Co-delivery of carbonic anhydrase IX inhibitor and doxorubicin as a promising approach to address hypoxia-induced chemoresistance. (31st December 2022) - Amin, Muhammad Umair; Ali, Sajid; Ali, Muhammad Yasir; Fuhrmann, Dominik C.; Tariq, Imran; Seitz, Benjamin S.; Preis, Eduard; Brüßler, Jana; Brüne, Bernhard; Bakowsky, Udo
Abstract: Hypoxia, an oxygen-deprived condition of the tumor, is one of the major reasons for resistance to chemotherapy. Carbonic anhydrases are generally involved in pH homeostasis in normal conditions, but in solid tumors having a strong relation with hypoxia, the carbonic anhydrase IX (CA-IX) enzyme is overexpressed and results in an extracellular acidic environment. For most weakly basic anticancer drugs, including doxorubicin (Dox), the ionization in an acidic environment limits their cellular uptake, and consequently, the tumor exposure to the drug at sub-therapeutic concentration comes out as chemoresistance. Herein, a combined drug delivery system of liposomes and mesoporous silica nanoparticles (MSNPs) was developed for the co-delivery of the CA-IX enzyme inhibitor and Dox in hypoxic condition. The unique structure of MSNPs with higher surface area was utilized for higher drug loading and sustained release of Dox. Additionally, the biocompatible nature of liposomal coating as a second loading site for the CA-IX enzyme inhibitor has provided gatekeeping effects at pore opening to avoid premature drug release. Lipid coated MSNPs as a co-delivery system for Dox and the CA-IX inhibitor have synergistic cytotoxic effects against MDA-MB 231 breast cancer cells in hypoxic conditions. These findings assure the potential of this drug delivery system to overcome hypoxia-related chemoresistance.